Merci Handy: From start-up to born-global?. (November 2019) - Boulocher-Passet, Véronique; Daly, Peter; Ruaud, Sabine
Two young, French entrepreneurs, Louis Marty and Roland Jais Nielsen, founded Merci Handy in 2014 with the objective of revolutionizing everyday cosmetics and internationalizing quickly. The case discusses the first steps of their international development and addresses the internationalization process of born-global companies. It also questions the benefits and opportunities of start-ups when addressing a global target.